Innovations in product design for fintech - Kalinina, O.; Yukhnova, K. (ХНЕУ, 2026)
The purpose of this study is to analyze modern innovations in product design for FinTech systems and to identify design approaches that improve usability, trust, adaptability of digital financial products.
Keywords: digital financial products